Principal's Leadership Style in Improving Teacher Performance and Motivation - Parlaungan Lubis; Zainuddi Zainuddi; Wildansyah Lubis (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2023)
The style or method of a school principal in his capacity as a leader will determine the success of improving teacher performance under his leadership. The purpose of this study was to analyze the principal's leadership style in improving teacher performance and motivation. This research was conducted at Madrasah Tsanawiyah Negeri 3 Aek Natas with a total of 58 respondents. Data collection techniques were carried out using interview, observation and documentation methods. Data analysis techniques are carried out with 3 paths, namely data reduction, data presentation, and drawing conclusions. The results showed that the principal's leadership style applied in schools was able to improve teacher performance. What the principal does is to set an example for the teacher and hold strict supervision and supervision of the teacher in carrying out teaching and learning tasks. The principal also gives appreciation to teachers who excel to be a motivation for other teachers. In terms of increasing teacher motivation, the principal provides a comfortable work environment where young teachers and senior teachers mingle with each other and senior teachers share experiences with young teachers, for example in terms of obtaining professional allowances such as teacher certification. The principal also provides high wages to honorary teachers so that they are able to meet the daily needs of teachers which has a positive impact on teachers because teachers are enthusiastic in carrying out the tasks assigned by the school